Exposure to PCB126 during the nursing period reversibly impacts early-life glucose tolerance - Rice, Brittany B.; Sammons, Keegan W.; Ngo Tenlep, Sara Y.; Weltzer, Madeline T.; Reynolds, Leryn J.; Rashid, Cetewayo S.; Swanson, Hollie I.; Pearson, Kevin J. (Frontiers in Endocrinology, 2023)
Polychlorinated biphenyls (PCBs) are persistent environmental organic pollutants that are known to have detrimental health effects. Using a mouse model, we previously demonstrated that PCB126 exposure before and during pregnancy and throughout the perinatal period adversely affected offspring glucose tolerance and/or body composition profiles. The purpose of this study was to investigate the glucose tolerance and body composition of offspring born to dams exposed to PCB126 during the nursing period only. Female ICR mice were bred and half of the dams were exposed to either vehicle (safflower oil) or 1 micromole PCB126 per kg of body weight via oral gavage on postnatal days (PND) 3, 10, and 17 (n = 9 per group). Weaning occurred on PND 21. Offspring body weight, lean and fat mass, and glucose tolerance were recorded every three weeks. PCB126 treatment did not alter dam nor offspring body weight (p > 0.05). PCB126-exposed male and female offspring displayed normal body composition (p > 0.05) relative to vehicle-exposed offspring. However, both male and female offspring that were exposed to PCB126 during the nursing period had significantly impaired glucose tolerance at 3 weeks of age (p < 0.05). At 12 weeks of age, no impairments in glucose tolerance existed in offspring (p > 0.05). Our earlier work suggests that in utero and postnatal PCB126 exposure predisposes offspring to having lower lean mass later in life. However, our current study shows that exposure to PCB126 through the mother's milk does not affect body composition but impairs glucose tolerance in the short-term.